Irradiation and bone marrow reconstitution affect the functional Ly49 natural killer cell repertoire in rats - Nestvold, Janne M.; Rolstad, Bent (Frontiers in Cell and Developmental Biology, 2015)
ABSTRACT Total body irradiation (TBI) is part of the preconditioning regimen for allogeneic bone marrow transplantation (alloBMT) and the procedure is associated with treatment-related toxicity and delayed immune reconstitution. Natural killer (NK) cells develop and acquire functional competence in close interaction with stromal bone marrow cells that are considered relatively radioresistant compared to the hematopoietic compartment. We thus undertook a study to assess the effect of TBI on the reconstitution of class I MHC-specific Ly49 NK cell receptors in a rat model of alloBMT. In rats subjected to TBI alone or followed by MHC-matched BMT, the irradiation conditioning induced a skewing of the Ly49 repertoire. Specifically, the activating Ly49s3bright subset exhibited increased frequency and receptor density which correlated with augmented alloreactivity relative to untreated control rats. Our results highlight the plasticity of NK cells and indicate that ionizing radiation (IR) affects the stromal compartment and as a consequence the maturation and functional properties of bone marrow-derived NK cells. These changes lasted throughout the 6 months observation period, showing that irradiation induces long term effects on the generation of the NK cell receptor repertoire.